Advances in Pacific Basin Business, Economics and Finance - Lee, Cheng-Few (Advances in Pacific Basin Business, Economics and Finance Series, 2023)
Advances in Pacific Basin Business, Economics and Finance(APBBEF) is an annual series designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries